Paulo Freire : une fenêtre ouverte vers les penseurs de la démocratie radicale - Yohan Dubigeon; Irène Pereira (Éducation et Socialisation)
The article is situated in the framework of a critical political philosophy in education, from which the place of radical democracy in education is questioned. For this, Paulo Freire is an inspiring figure to think about the place of the notion of “radical democracy” in education and of education for a radical citizenship. But from this, it is possible to open up to other works and authors relevant to think about radical democracy in education, among which Jacques Rancière and Cornelius Castoriadis. In Rancière, the postulate of radical equality of intelligences constitutes the foundation. In Castoriadis, it is the notions of paideia and praxis that articulate education, autonomy and the exercise of a “radically” democratic citizenship where everyone learns to be both governed and governing. The article proposes to introduce in educational sciences the contemporary debates related to radical democracy.